Profil Kemampuan Berpikir Kritis Mahasiswa dalam Menyelesaikan Soal Pemecahan Masalah Matematika Ditinjau dari Jenis Kelamin - Dwi Utami Setyawati; Baiq Rika Ayu Febrilia; Ita Chairun Nissa (Universitas Syiah Kuala, 2020)
Critical thinking is a careful and calculated thinking activity using complex reasoning. The purpose of this study is to describe the students' ability to think critically in solving problems based on gender. The research subjects were two second semester students of Mathematics Education Program Universitas Pendidikan Mandalika. The instruments were a mathematics problem-solving sheet and interview guidelines. Data were analyzed qualitatively by three stages: data reduction, data presentation, and concluding. The results of the study found that the two subjects could bring up the five indicators of critical thinking. The male student was better in providing analytical analysis on the further explanation of the solution given, and the female student was better providing a complete, clear and detailed explanation so that it takes a longer time. However, the two students could not accurately draw conclusions and analysis. It is recommended that the lecturer provides various questions with different levels so that students are accustomed to thinking critically and they, later, as teachers also can train students' critical thinking.